2011
DOI: 10.1002/ctpp.201010119
|View full text |Cite
|
Sign up to set email alerts
|

New Model of Dusty Plasma Particles Interaction

Abstract: The main goal of this report is to obtain the macropotentials of dusty plasma particles interactions which account for the collective events in the medium and, then, to analyze their dependence on plasma parameters. It is shown that the attraction between conductive dust grains turns possible due to the polarization phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…For example, right above this pseudopotential model has been used in the hypernetted chain approximation to study the radial distribution functions of dust grains which has revealed the non-monotonic behavior at sufficiently large values of the coupling parameter corresponding to a short-or even long-range order formation in the dust component of the plasma. This work is a extension of [10] where the similar procedure was utilized to describe the interaction of all plasma components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, right above this pseudopotential model has been used in the hypernetted chain approximation to study the radial distribution functions of dust grains which has revealed the non-monotonic behavior at sufficiently large values of the coupling parameter corresponding to a short-or even long-range order formation in the dust component of the plasma. This work is a extension of [10] where the similar procedure was utilized to describe the interaction of all plasma components.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the generalized Poisson-Boltzmann equation can be strictly derived from the Bogolyubov hierarchy for the equilibrium distribution functions in the pair correlation approximation [7]. Moreover, in the past decade it was successfully applied to a variety of kinds of plasmas, such as semiclassical plasmas [8], partially ionized plasmas [9] and even dusty plasmas in the Debye approximation [10].…”
Section: Interaction Model Of Two Isolated Dust Particlesmentioning
confidence: 99%
“…It should directly be stressed that the generalized Poisson-Boltzmann equation can rigorously be derived from the Bogolyubov chain of equations for the equilibrium distribution functions in the pair correlation approximation 31 and in the recent past it was successfully applied to a variety of plasmas, such as the semiclassical plasma, 32,33 the partially ionized hydrogen plasma, 34,35 and even the dusty plasma in the Debye approximation. 36,37 Equation (12) is actually a relation to determine the effective interaction potential, or the pseudopotential, U ab , through the true microscopic potentials u ab . It can be clearly seen that the pseudopotentials definitely take into account the screening in the buffer plasmas since they inevitably incorporate the number densities of electrons and protons.…”
Section: Plasma Parametersmentioning
confidence: 99%
“…Note that the generalized Poisson-Boltzmann equation can be strictly derived from the Bogolyubov hierarchy for the equilibrium distribution functions in the pair correlation approximation [21]. Moreover, in the past decade it was successfully applied to a variety of plasmas, such as semiclassical [22], partially ionized [23,24] or even dusty plasmas in the Debye approximation [25]. Some of those results were then successfully used to neatly describe experimental data on X-ray scattering in dense plasmas [26,27].…”
Section: Wwwcpp-journalorgmentioning
confidence: 99%